2018
DOI: 10.1007/s00167-018-4870-1
|View full text |Cite
|
Sign up to set email alerts
|

Completion repair exhibits increased healing characteristics compared with in situ repair of partial thickness bursal rotator cuff tears

Abstract: Despite the concerns of detaching the intact tendon, the completion repair technique exhibited increased healing characteristics compared with the in situ technique. The reason for this finding might be the refreshing effect of debridement at the chronic degenerated tendon that could improve the healing response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Interestingly, there have been studies on live animals that seem to show that tear completion and repair of partial-thickness rotator cuff tears provide better healing compared with in situ repair, in rabbits 30 and in rats. 31 We believe that the technique described here represents a reproducible and effective method in addressing small rotator cuff tears in which the bony footprint of the tendon is small, not visible at all, or covered with remnant tendon, and hence medial row anchors are not required. The use of a single lateral row repair technique often requires a mattress suture configuration, which can sometimes cause suture cutouts in degenerated tendons.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, there have been studies on live animals that seem to show that tear completion and repair of partial-thickness rotator cuff tears provide better healing compared with in situ repair, in rabbits 30 and in rats. 31 We believe that the technique described here represents a reproducible and effective method in addressing small rotator cuff tears in which the bony footprint of the tendon is small, not visible at all, or covered with remnant tendon, and hence medial row anchors are not required. The use of a single lateral row repair technique often requires a mattress suture configuration, which can sometimes cause suture cutouts in degenerated tendons.…”
Section: Discussionmentioning
confidence: 89%
“…This method is convenient and easily mastered by most surgeons [ 20 ]. In addition, animal experiments have shown that full-thickness suturing has better outcomes than in situ repair, which may be related to the more thorough debridement that is done in full-thickness suturing [ 21 ]. However, Jordan et al reviewed and summarized the clinical efficacy of these two methods and concluded that the trans-tendon technique resulted in more obvious pain and motion limitations at the early stage of recovery, although both methods eventually achieved satisfactory clinical efficacy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 In contrast, evidence of the potential for superior biological healing after TCR versus TTR has been observed via published animal models. 14 Regardless of the chosen technique, the involved tendon should be adequately debrided of degenerative tissue before repair is attempted.…”
Section: Discussionmentioning
confidence: 99%